Isoliquiritigenin Inhibits Cigarette Smoke-Induced COPD by Attenuating Inflammation and Oxidative Stress via the Regulation of the Nrf2 and NF-κB Signaling Pathways - Yu, Duo; Liu, Xueshibojie; Zhang, Guangxin; Ming, Zhihui; Wang, Tiejun (Frontiers in Pharmacology, 2018)
Chronic obstructive pulmonary disease (COPD) is the major leading cause of disease with high-mortality worldwide. Cigarette smoke (CS) is a major factor for COPD. CS causes chronic inflammation and oxidative stress, which contributes to lung dysfunction in COPD. Isoliquiritigenin (ILG), a natural flavonoid derived from the root of liquorice, has been reported to possess antiinflammatory and antioxidant activity. In the present study, we tested the mechanism and protective effects of ILG on CS-induced COPD. Mice were exposed to CS for 2 h twice a day for 4 weeks. ILG was given orally 1 h before CS exposure twice a day for 4 weeks. The bronchial alveolar lavage fluid was collected to test the levels of inflammatory cytokines and the number of inflammatory cells. The lung tissues were obtained to evaluate the pathological changes, lung edema, myeloperoxidase (MPO) activity, malondialdehyde (MDA) level, as well as the expression of the nuclear factor-erythroid 2 (Nrf2) and nuclear factor κB (NF-κB) signaling pathways. The results showed that ILG reduced the infiltration of inflammatory cells and the production of inflammatory cytokines. ILG also reversed CS-induced lung pathological injuries, wet/dry ratio, MPO activity, and MDA level. Further research also showed that ILG dose-dependently up-regulated the expression of Nrf2 and down-regulated the expression of NF-κB signaling pathways induced by CS. In conclusion, ILG protected against CS-induced COPD by inhibiting inflammatory and oxidative stress via the regulation of the Nrf2 and NF-κB signaling pathways.